Controller Design of UPQC for Enhancing Power Quality in Distribution System - Kittaya Somsai (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents the procedure of PI controller design of Unified Power Quality Conditioner (UPQC) for improving power quality in the distribution system. A mathematical model of the distribution system with the UPQC is thoroughly explained in this paper. The mathematical model that is founded has been used for designing the PI controller. In order to investigate the dynamic performance and design the controller, linear approximation technique is used. Linearization of the systems that is around the operating point provides a set of linear equations, and then multi-input multi-output (MIMO) transfer functions of the systems are obtained. Two controller design techniques are presented and compared. One is the sequential loop closure controller design with parameter tuning through the Bode diagram (SLC-BD). The other one is the controller optimization design with the genetic algorithms (CO-GA). The performances of these techniques are verified and compared by using MATLAB program. Simulation results reveal that the power quality in the distribution system can be enhanced by using UPQC with the proposed controller design.